Correlation of HDL cholesterol serum and Wagner’s severity level of diabetic foot ulcers - Kartono, Tommy; Mallapasi, Muhammad Nuralim; Mulawardi, Mulawardi; Laidding, Sachraswaty R.; Aminyoto, Meiliati; Prihantono, Prihantono (International Journal of Research in Medical Sciences, 2017)
Background: Diabetic foot ulcers are one of the leading causes of amputation in non-traumatic patients. This research aimed to investigate the correlation between the level of HDL cholesterol and the severity level of diabetic foot ulcer based on Wagner classification. The study conducted at Wahidin Sudirohusodo Hospital, Makassar, Indonesia. Methods: This is an observational study with the cross-sectional design. The data collected before and after the treatment. The change of the levels of HDL cholesterol and the severity level of the diabetic foot ulcer based on Wagner classification during the treatment were analyzed. Data analyzed using Spearman Correlation test, the paired t-test to assess the change in the levels of HDL cholesterol and the levels of severity of diabetic foot ulcer based on Wagner classification at the time admission and after the treatment. ANOVA test was used to observe the reduction significance of the severity of diabetic foot ulcer based on Wagner classification, and it was categorized as significant if p<0.05. Results: The results indicated that there is a correlation between the level of HDL cholesterol and the severity level of diabetic foot ulcer based on Wagner classification either at the early treatment with p-value = 0.003 (r = - 0.448) and the end of the treatment with p-value = 0.001(r = - 0.477). The lower of the level of cholesterol HDL, the higher was the severity level of the diabetic foot ulcer. Meanwhile, the correlation between the increase of the level of HDL cholesterol and the reduction of Wagner classification during the treatment was statistically insignificant with p-value = 0.100 (r = - 0.215). Conclusions: there was a correlation between elevated HDL cholesterol levels during treatment with Wagner classification decrease during treatment, the higher the HDL change, the higher the Wagner classification, but this was weak correlation and statistically insignificant.